Immune Checkpoint Inhibition in Sepsis: A Phase 1b Randomized, Placebo-Controlled, Single Ascending Dose Study of Antiprogrammed Cell Death-Ligand 1 Antibody (BMS-936559)*. Issue 5 (May 2019) - Hotchkiss, Richard S.; Colston, Elizabeth; Yende, Sachin; Angus, Derek C.; Moldawer, Lyle L.; Crouser, Elliott D.; Martin, Greg S.; Coopersmith, Craig M.; Brakenridge, Scott; Mayr, Florian B.; Park, Pauline K.; Ye, June; et al.
Abstract : Objectives: To assess for the first time the safety and pharmacokinetics of an antiprogrammed cell death-ligand 1 immune checkpoint inhibitor (BMS-936559; Bristol-Myers Squibb, Princeton, NJ) and its effect on immune biomarkers in participants with sepsis-associated immunosuppression. Design: Randomized, placebo-controlled, dose-escalation. Setting: Seven U.S. hospital ICUs. Study Population: Twenty-four participants with sepsis, organ dysfunction (hypotension, acute respiratory failure, and/or acute renal injury), and absolute lymphocyte count less than or equal to 1, 100 cells/μL. Interventions: Participants received single-dose BMS-936559 (10–900 mg; n = 20) or placebo ( n = 4) infusions. Primary endpoints were death and adverse events; key secondary endpoints included receptor occupancy and monocyte human leukocyte antigen-DR levels. Measurements and Main Results: The treated group was older (median 62 yr treated pooled vs 46 yr placebo), and a greater percentage had more than 2 organ dysfunctions (55% treated pooled vs 25% placebo); other baseline characteristics were comparable. Overall mortality was 25% (10 mg dose: 2/4; 30 mg: 2/4; 100 mg: 1/4; 300 mg: 1/4; 900 mg: 0/4; placebo: 0/4). All participants had adverse events (75% grade 1–2). Seventeen percent had a serious adverse event (3/20 treated pooled, 1/4 placebo), with none deemed drug-related. Adverse events that were potentially immune-related occurred in 54% of participants; most were grade 1–2, none required corticosteroids, and none were deemed drug-related. No significant changes in cytokine levels were observed. Full receptor occupancy was achieved for 28 days after BMS-936559 (900 mg). At the two highest doses, an apparent increase in monocyte human leukocyte antigen-DR expression (> 5, 000 monoclonal antibodies/cell) was observed and persisted beyond 28 days. Conclusions: In this first clinical evaluation of programmed cell death protein-1/programmed cell death-ligand 1 pathway inhibition in sepsis, BMS-936559 was well tolerated, with no evidence of drug-induced hypercytokinemia or cytokine storm, and at higher doses, some indication of restored immune status over 28 days. Further randomized trials on programmed cell death protein-1/programmed cell death-ligand 1 pathway inhibition are needed to evaluate its clinical safety and efficacy in patients with sepsis. Abstract : Supplemental Digital Content is available in the text.